Identifikasi Kelelawar Pemakan Buah Asal Sulawesi Berdasarkan Morfometri (THE MORPHOMETRIC IDENTIFICATION OF CELEBES FRUIT BATS) - Ransaleleh, Tiltje Andretha; Maheswari, Rarah Ratih Adjie; Sugita, Purwantiningsih; Manalu, Wasmen (Jurnal Veteriner, 2013)
The bat is very important for human life, because of their  role as pollinator of plants, as a producer oforganic fertilizer,  and as food.  In Northern Celebes fruit eating bats serve as exotic food, so the presenceof bats were threatened to be extinct due to uncontrolled hunting.  The changes of the forest for plantationlands, damage the habitats and the bats were forced to migrate out.   The aim of the study was to identifythe fruit eating bats of Celebes.  Morphometry of body size, skull,  and physical characteristics were usedin determining the types and distribution  of fruit eating bats in Celebes. The field survey was carried outat the hunting area, bat dealers, and bat sellers. The collected data were analyzed by using descriptivemethod and interpreted by narrating to describe the entire study. The result show that  there were fivetypes of fruit eating bats : i.e.  kalong sulawesi (Acerodon celebensis),  paniki pallas (Nyctimene cephalotes),codot wallet (Thoopterus nigrescens), nyap biasa (Rousettus amplexicaudatus), and  kalong hitam  (Pteropusalecto).
Keywords: fruit eating bats, morphometric, identification